2020
DOI: 10.12968/jowc.2020.29.sup7.s44
|View full text |Cite
|
Sign up to set email alerts
|

Use of a bacterial fluorescence imaging system to target wound debridement and accelerate healing: a pilot study

Abstract: Objective: Optimal wound-bed preparation consists of regular debridement to remove devitalised tissues, reduce bacterial load, and to establish an environment that promotes healing. However, lack of diagnostic information at point-of-care limits effectiveness of debridement. Method: This observational case series investigated use of point-of-care fluorescence imaging to detect bacteria (loads >104CFU/g) and guide wound bed preparation. Lower extremity hard-to-heal wounds were imaged over a 12-week period fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…The inclusion of FL as part of routine wound assessment provided information on bacterial burden that led to additional improvements in care: Guided wound bed preparation in ≥90% of wounds in this and other studies. 35 , 52 Information on location of bacterial burden at point of care has been shown to be highly impactful for debridement, 52 , 53 selection of appropriate cleanser, 30 and general wound bed preparation before application of advanced therapies. 30 Advanced therapies such as cellular and tissue-based products and skin grafts often fail when high bacterial loads are present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion of FL as part of routine wound assessment provided information on bacterial burden that led to additional improvements in care: Guided wound bed preparation in ≥90% of wounds in this and other studies. 35 , 52 Information on location of bacterial burden at point of care has been shown to be highly impactful for debridement, 52 , 53 selection of appropriate cleanser, 30 and general wound bed preparation before application of advanced therapies. 30 Advanced therapies such as cellular and tissue-based products and skin grafts often fail when high bacterial loads are present.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from small longitudinal observational studies demonstrate accelerated wound area reduction with use of FL. 32 , 53 Due to the limited (1.5 mm) depth of excitation 36 and inability to detect non-porphyrin-producing bacteria, including species from the Streptococcus , Enterococcus , and Finegoldia generas (which account for an estimated 12% of the most prevalent wound pathogens 23 and rarely occur monomicrobially 69 ), it is recommended that FL be used in combination with CSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether PA would ever express solely porphyrins, not pyoverdines, in a wound environment has, to our knowledge, not been studied. If this were to occur then red fluorescence would presumably be used to guide bacterial removal treatments, as it does for other pathogens [ 27 , 45 , 67 ]. Given the association between pyoverdine production and PA virulence [ 36 , 37 , 38 , 39 ], detection of wounds in which PA is expressing this virulence factor has large clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have specifically shown that fluorescence imaging can change treatment plans, in one study in as many as 73% of cases [ 7 , 36 ]. Even more encouraging is that the use of fluorescence imaging to inform the location and extent of debridement to target bacterial habitation in recalcitrant wounds has been shown to increase healing rates [ 71 ], which is the ultimate goal for most wound care. Other groups illustrated that the overall incorporation of fluorescence imaging into patient care can change the trajectory of wound healing, leading to interventions that placed non-healing wounds on a healing trajectory [ 72 ] or healed more wounds altogether [ 73 ].…”
Section: Impact Of Fluorescence Imaging On Wound Care Including Bmentioning
confidence: 99%